Precarious talent : highly skilled Chinese and Indian immigrants in Singapore - Zhan, Shaohua (2020)
This paper examines the challenges that highly skilled immigrant workers face and their strategies of adaptation. We employ the term “precarious talent” to capture an often neglected aspect of skilled migration. Using both survey data and interviews on skilled Chinese and Indian immigrants in Singapore, we find that these migrants confront varying degrees of employment insecurity and settlement uncertainty in an era of neoliberal globalization, contrary to the common perception of “foreign talent” as a privileged group. We also find that skilled immigrants actively use Information and Communication Technologies (ICTs) to mitigate precarity: they use the Internet and social media to access timely job information, sustain social contacts across national borders, and adapt to life and work in the host society. However, the ability to effectively cope with precarity depends on their own socioeconomic status, context of reception, and homeland development. We discuss theoretical implications of our findings.